2013
DOI: 10.1097/wnr.0b013e32835c93e3
|View full text |Cite
|
Sign up to set email alerts
|

Modality-match effect in false recognition

Abstract: In the Deese-Roediger-McDermott (DRM) paradigm, participants falsely recall or recognize a nonpresented word (critical lure), highly associated with previously studied words. As numerous DRM studies have found a robust false memory effect at the behavioural level, event-related potentials (ERPs) studies have searched for possible overlapping in brain electrical activity between true and false memory. Using the DRM paradigm, the present experiment manipulated the sensory modality of stimulus presentation (audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
1
18
0
3
Order By: Relevance
“…Goldmann et al (2003) proposed that post-retrieval control may be critical based on the finding that late, right frontal ERP old/new effects differed between items correctly and falsely judged "old", both of which also elicited parietal effects (see above). However, other studies have not found such a difference Duzel et al, 1997;Nessler et al, 2001;Boldini et al, 2013;Beato et al, 2012;Wiese and Daum, 2006; see also Cheng and Rugg (2004)). A fuller answer to the question of how people successfully distinguish between studied items b r a i n r e s e a r c h 1 6 2 4 ( 2 0 1 5 ) 3 3 6 -3 4 8 and lures requires examination of how correctly rejected lures are processed, and how this processing differs from that of lures incorrectly judged "old".…”
Section: Erp Studies Of False Recollectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldmann et al (2003) proposed that post-retrieval control may be critical based on the finding that late, right frontal ERP old/new effects differed between items correctly and falsely judged "old", both of which also elicited parietal effects (see above). However, other studies have not found such a difference Duzel et al, 1997;Nessler et al, 2001;Boldini et al, 2013;Beato et al, 2012;Wiese and Daum, 2006; see also Cheng and Rugg (2004)). A fuller answer to the question of how people successfully distinguish between studied items b r a i n r e s e a r c h 1 6 2 4 ( 2 0 1 5 ) 3 3 6 -3 4 8 and lures requires examination of how correctly rejected lures are processed, and how this processing differs from that of lures incorrectly judged "old".…”
Section: Erp Studies Of False Recollectionmentioning
confidence: 99%
“…Dennis et al's (2012) recent functional magnetic resonance imaging (fMRI) study also showed hippocampal (as opposed to parahippocampal) and early visual cortical activity both distinguished true from false recollection, in line with the view that contextual reinstatement may accompany only veridical recollective experience (see also Cabeza et al (2001), Okado and Stark (2003) and Karanian and Slotnick (2014)). However, numerous other ERP studies have found that false as well as true recognition can elicit parietal old/new effects, suggesting occurrence of false recollection when studied items and lures are visually similar pictures sharing basic-level category membership (Curran and Cleary, 2003;Goldmann et al, 2003) as well as in adaptations of the Deese-Roediger-McDermott (DRM) paradigm (Boldini et al, 2013;Curran et al, 2001;Nessler et al, 2001;Beato et al, 2012;Wiese and Daum, 2006; see also Cheng and Rugg (2004)). These data are consistent with other fMRI and PET studies which have found indistinguishable neural correlates of true and false recognition (e.g., Kahn et al, 2004;Kim and Cabeza, 2007).…”
Section: Erp Studies Of False Recollectionmentioning
confidence: 99%
“…Initially, the DRM lists used in the study of false memories were FAS lists (e.g., Boldini, Beato, Cadavid, 2013;Gallo & Roediger, 2002;Roediger & McDermott, 1995;Stadler, Roediger, & McDermott, 1999), characterized by the fact that the critical words produced the studied words in free association tasks. However, subsequent research suggested that BAS (the associative strength from the studied items to the critical words) is the best predictor of false memories (e.g., Deese, 1959;Howe, Wimmer, & Blease, 2009;McEvoy et al, 1999;Robinson & Roediger, 1997;Roediger, Balota, & Watson, 2001).…”
mentioning
confidence: 99%
“…The second planned analysis focused on ERP data from right frontal sites between 800 and 1,400 ms to assess the impact of Response Type and Valence on the ERP correlate of postretrieval monitoring. These sites were selected on the basis of studies localising ERP correlates of postretrieval monitoring to right frontal sites (Cruse & Wilding, 2009; Donaldson & Rugg, 1998; Johnson et al, 1997; Wilding & Rugg, 1996) and more recent studies performing targeted analyses of these effects at the same (or subset of) right frontal sites as those analysed here (Beato, Boldini, & Cadavid, 2012; Boldini, Beato & Cadavid, 2013; Cadavid & Beato, 2016; Rosburg et al, 2011). Figure 4 indicates that neutral target hits were more positive going than either neutral CRs or neutral nontarget CRs at right frontal sites between 800 and 1,400ms.…”
Section: Resultsmentioning
confidence: 99%